In Vitro Assessment of Wound-Healing Efficacy of Stabilized Basic Fibroblast Growth Factor (FGF-2) Solutions - Leah Benington; Jingxin Mo; Mingxin Li; Gunesh Rajan; Cornelia Locher; Lee Yong Lim (MDPI AG, 2024)
Chronic tympanic membrane perforations (TMP) pose a significant clinical challenge, but basic fibroblast growth factor (FGF-2) shows promise for their treatment, despite its instability in aqueous solutions which hampers the sustained delivery crucial for the healing process. Addressing this, our research focused on the development of stabilized FGF-2 formulations, F5 and F6, incorporating dual, generally regarded as safe (GRAS) excipients to enhance stability and therapeutic efficacy. F5 combined FGF-2 (1600 ng/mL) with 0.05% w/v methylcellulose (MC) and 20 mM alanine, while F6 used FGF-2 with 0.05% w/v MC and 1 mg/mL human serum albumin (HSA). Our findings demonstrate that these novel formulations not only significantly improve the cytoproliferation of human dermal fibroblasts but also exhibit the most potent chemoattractant effects, leading to the highest fibroblast monolayer closure rates (92.5% for F5 and 94.1% for F6 within 24 h) compared to other FGF-2 solutions tested. The comparable performance of F5 and F6 underscores their potential as innovative, less invasive, and cost-effective options for developing otic medicinal products aimed at the effective treatment of chronic TMP.